LbKAT3 may assist in mycorrhizal potassium uptake, and overexpression of LbKAT3 may promote potassium, phosphorus, and water transport from arbuscular mycorrhizal fungi to the host plant - Han, Xia; Zhou, Yuhao; Li, Yanpeng; Ren, Wei; Liu, Kunkun; Zhang, Wenrui; Zhang, Haoqiang; Tang, Ming (Frontiers in Plant Science, 2023)
Potassium plays important roles in most plant physiological processes. Arbuscular mycorrhizal (AM) fungi promote plant water and mineral nutrient acquisition to promote plants growth. However, fewer study focused on the effect of AM colonization on potassium uptake of host plants. In this study, the effect of an AM fungus (Rhizophagus irregularis) and potassium condition (0 mM, 3 mM, 10 mM K+) on Lycium barbarum were evaluated. The split-root test was studied, and the potassium uptake capacity of LbKAT3 was verified in yeast. Moreover, overexpressed LbKAT3 tobacco was constructed, and studied the mycorrhizal function of the tobacco under different potassium conditions (0.2 mM and 2 mM K+). Inoculation of R. irregularis and application of potassium increased dry weight, and potassium and phosphorus contents of L. barbarum, and they also increased colonization rate and arbuscule abundance of R. irregularis. And they up-regulated the expression of LbKAT3, AQPs in L. barbarum, while inoculation of R. irregularis induced LbPT4, and Rir-AQP1 and Rir-AQP2 expression and application of potassium up-regulated the expression of them. The LbKAT3, has certain potassium uptake capacity, and AM fungi locally regulated its expression. Moreover, inoculation of R. irregularis can improve growth, potassium and phosphorus contents, and induced NtPT4 and Rir-AQP1 and Rir-AQP2 expression in overexpressed (OE) LbKAT3 tobacco under potassium deficient condition. Overexpression of LbKAT3 in tobacco improved growth and potassium accumulation of tobacco, AM colonization, and up-regulated the expression of NtPT4 and Rir-AQP1. The results suggested that LbKAT3 may assist in mycorrhizal potassium uptake, and overexpression of LbKAT3 may promoted potassium, phosphorus and water transport from AM fungi tobacco under potassium deficiency condition.